Radiofrequency or cryoballoon ablation for index pulmonary vein isolation: What is the impact on long‐term clinical outcomes after repeat ablation?. (15th March 2020) - Inaba, Osamu; Metzner, Andreas; Rottner, Laura; Mathew, Shibu; Lemes, Christine; Maurer, Tilman; Heeger, Christian; John, Alexander; Hashiguchi, Naotaka; Wohlmuth, Peter; Ouyang, Feifan; Kuck, Karl‐Heinz; et al.
Abstract: Aims: The current study sought to assess the impact of the utilized energy source during index ablation on long‐term clinical outcomes after repeat ablation of atrial fibrillation (AF). Index ablation procedures were either performed using radiofrequency current (RFC) (RFC group) or cryoballoon (CB) ablation (CB group). Repeat ablation was performed by the use of RFC. Methods: A total of 195 patients (138 RFC group; 57 CB group) with paroxysmal AF were included. All patients had a recurrence of AF following the index ablation procedure. Freedom from AF was estimated with the Kaplan‐Meier method. Results: After a 3 years follow‐up, the estimated arrhythmia‐free survival did not differ between the two groups (RFC group 48% vs CB group 47%, P = .78). During index ablation, procedure times were significantly shorter in the CB group (95 [80, 140] vs 140 [115, 164] minutes, P ≤ .001), whereas fluoroscopy times (16 [11; 22] vs 19 [14; 25] minutes, P = .003), the dose area product (1862 [1203; 2922] vs 3148 [1756; 5888] cGycm 2, P ≤ .001) and the amount of contrast dye (92 ± 32 vs 123 ± 33 mL, P ≤ .001) were significantly lower in the RFC group. During repeat ablation, procedure times were significantly shorter in patients being initially treated with RFC (115 [85; 145] vs 125 [105; 150] minutes, P = .007). There was a trend towards a higher pulmonary vein reconnection rate in the RFC group without meeting statistical significance ( P = .074). Conclusions: In patients with repeat ablation of AF, index RFC or CB ablation are equally effective in terms of freedom from AF. Although CB ablation results in shorter index procedures times, durations of repeat ablation are significantly longer.